Different Strokes of Creativity: Personality and Entrepreneurial Intent Among Workers of Telecom Industry in Nigeria - Sunday, Fasanmi, Samuel; Muhibat, Osungboye, Biola (European Scientific Journal, ESJ, 2018)
The study examined personality traits as predictors of entrepreneurial intention among managers of telecom industries in Nigeria. Opinions of two hundred and five (205) respondents were randomly sampled across various offices of Globacom Plc in Lagos State, Nigeria. A battery of standardized tests was administered on them using a cross-sectional survey research design. One hypothesis was tested in the study. Results revealed that extraversion (β =0.147, t = 2.582; P < .05), neuroticism (β = -.271, t = 4.358; P< .05), openness to experience (β =.224, t =3.456; P<.05) are significantly independently predicted entrepreneurial intention among managers of telecom industries in Nigeria. It was also found out that extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience significantly and jointly predicted entrepreneurial intention among managers of telecom industries in Nigeria F (6, 204) = 24.895; P < .05, R2 = .413. Results were discussed in line with the literature. It was recommended that since this study has established a strong relationship between personality traits and entrepreneurial intentions, telecom industries should as a matter of urgency include personality identification in their training regimen, this will go a long way in bringing fulfillment to managers , and consequently better the lots of their companies.